2019
DOI: 10.1136/openhrt-2019-001108
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for the ASSAIL-MI-trial: a randomised controlled trial designed to assess the effect of tocilizumab on myocardial salvage in patients with acute ST-elevation myocardial infarction (STEMI)

Abstract: IntroductionInterleukin-6 (IL-6) may be involved in ischaemia-reperfusion injury and myocardial remodelling after myocardial infarction (MI). We have recently shown that IL-6 inhibition by tocilizumab attenuates systemic inflammation and troponin T-release in patients with acute non-ST elevation MI (NSTEMI). Experimental studies suggest that IL-6 inhibition can limit infarct size through anti-inflammatory mechanisms, but this has not been tested in clinical studies. With the ASSessing the effect of Anti-IL-6 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 38 publications
(43 reference statements)
0
22
0
Order By: Relevance
“…The results showed a negligible effect on the level of IL-1 β and IL-6 and the number of MACE [ 68 ]. Similarly, ACS patients administered with the IL-6 inhibitor tocilizumab showed a reduced level of troponin and inflammatory markers in the ASSessing the Effect of Anti-IL-6 Treatment in MI (ASSAIL-MI) trial [ 16 , 69 , 70 ], which was designed to assess the effects of tocilizumab on ischemia reperfusion injury in patients with ST-elevation myocardial infarction. The neutral results in the CIRT trial suggest that future targeted inflammatory therapies should focus on the control of specific inflammatory cytokines or immune cells [ 16 ].…”
Section: Therapeutic Approaches Targeting Immune and Inflammationmentioning
confidence: 99%
“…The results showed a negligible effect on the level of IL-1 β and IL-6 and the number of MACE [ 68 ]. Similarly, ACS patients administered with the IL-6 inhibitor tocilizumab showed a reduced level of troponin and inflammatory markers in the ASSessing the Effect of Anti-IL-6 Treatment in MI (ASSAIL-MI) trial [ 16 , 69 , 70 ], which was designed to assess the effects of tocilizumab on ischemia reperfusion injury in patients with ST-elevation myocardial infarction. The neutral results in the CIRT trial suggest that future targeted inflammatory therapies should focus on the control of specific inflammatory cytokines or immune cells [ 16 ].…”
Section: Therapeutic Approaches Targeting Immune and Inflammationmentioning
confidence: 99%
“…However, our results indicate that, among hundreds of circulating proteins not routinely assayed in clinical setting of MI, IL-6 and ST2 appear to potentially carry valuable prognostic information. Ongoing randomized trials of tocilizumab, a monoclonal antibody targeting IL-6 receptors may add further insight 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, since none of the trials reported significant adverse events associated with the treatment, investigation on this topic is still ongoing. In particular, the “ASSessing the effect of Anti-IL-6 treatment in MI” (ASSAIL-MI) trial [ 12 ] was recently completed, and its results are awaited. Compared to previous trials, the ASSAIL-MI enrolled patients with STEMI and aimed at investigating, as a primary endpoint, the effects of tocilizumab on myocardial salvage, evaluated through cardiac magnetic resonance imaging.…”
Section: From Bench To Bedside: Targeting Cytokines In CV Clinical Trmentioning
confidence: 99%